Enhanced selective copper precipitation by mechanochemically activated benzene tricarboxylic acid. Issue 12 (25th May 2023) - Shi, Qing; Yan, Shanshan; Wang, Chao; Zeng, Chaocheng; Hu, Huimin; Chen, Mengfei; Chen, Min; Zhang, Qiwu
ABSTRACT: Toward the treatment of waste solution containing heavy metals, direct precipitation of the metal ions from an acidic solution without alkaline neutralisation is still the greatest challenge. Based on the ligand properties of benzene tricarboxylic acid (BTC) to copper ions, a simple ball milling with 90 min at 400 rpm was used to activate BTC to enhance its capacity for copper removal from the pH of the original solution around 3–4. A set of analytical methods were used to characterise the activated BTC sample and BTC-Cu precipitate before and after copper precipitation. Compared with the raw BTC, the activated BTC could efficiently remove copper ions over 90% from an initial copper concentration of 100 mg/L in a shorter time from an acidic media with lower pH of around 2.60 and the maximum adsorption capacity can be stable at about 111.70 mg/g, resulting from probably the enhanced deprotonation effect for copper incorporation. Furthermore, at controlled dosage, the activated BTC demonstrated much high selectivity on precipitating copper ions from other heavy metals of Ni, Mn, Zn and Cd and provided a new approach for easy copper recycling from waste solution as secondary sources. This process may serve the purpose of recycling both metal and acidic solutions after the purification. GRAPHICAL ABSTRACT: UF0001